2018
DOI: 10.15283/ijsc18002
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Stem Cells and Gene Transfected Stem Cells Therapy on the Pancreas of Experimentally Induced Type 1 Diabetes

Abstract: Background and Objectives: Insulin secretion entirely depends on Ca 2+ influx and sequestration into endoplasmic reticulum (ER) of β-cells, performed by Sarco-ER Ca 2+-ATPase 2b (SERCA2b). In diabetes, SERCA2b is decreased in the β-cells leading to impaired intracellular Ca 2+ homeostasis and insulin secretion. Adipose mesenchymal stem cells (AMSCs) play a potential role in transplantation in animal models. The present study aimed at investigating and comparing the therapeutic effect of non-transfected AMSCs a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…it has been reported that Serca2b regulates er stress (19), which is attenuated in pancreatic β-cells (20). A previous study has indicated that SERCA2 exerts protective effects by regulating HG-treated er stress and apoptosis in podocytes (19). Therefore, the present study aimed to investigate the role and function of GAS5 and SERCA2b in DR.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…it has been reported that Serca2b regulates er stress (19), which is attenuated in pancreatic β-cells (20). A previous study has indicated that SERCA2 exerts protective effects by regulating HG-treated er stress and apoptosis in podocytes (19). Therefore, the present study aimed to investigate the role and function of GAS5 and SERCA2b in DR.…”
Section: Introductionmentioning
confidence: 91%
“…Serca2b is located at the sarcoplasmic reticulum or er membrane of all types of cells and is responsible for maintaining intracellular ca 2+ homeostasis. it has been reported that Serca2b regulates er stress (19), which is attenuated in pancreatic β-cells (20). A previous study has indicated that SERCA2 exerts protective effects by regulating HG-treated er stress and apoptosis in podocytes (19).…”
Section: Introductionmentioning
confidence: 95%
“…In that study, analysis of miRNA expression the differentiation of hepatocytes to insulin-producing cells was associated with the BMP/Smad signaling pathway rather than the Wnt/β-catenin signaling pathway [ 76 ]. More recently, transfection of Sarco-ER Ca 2+ -ATPase 2b gene in adipose mesenchymal stem cells exhibited a significant therapeutic effect in a mouse model of type 1 diabetes [ 77 ]. Recent reports also showed the effect of FGF21 gene therapy on a high-fat-diet mouse model where treatment was associated with significant reductions in body weight, adipose tissue hypertrophy, insulin resistance, hepatic steatosis, inflammation, and fibrotic changes [ 78 ].…”
Section: Diabetes Mellitusmentioning
confidence: 99%